2021
DOI: 10.1002/1878-0261.13047
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer metastasis: immune profiling of lymph nodes reveals exhaustion of effector T cells and immunosuppression

Abstract: Sentinel lymph nodes are the first nodes draining the lymph from a breast and could reveal early changes in the host immune system upon dissemination of breast cancer cells. To investigate this, we performed single‐cell immune profiling of lymph nodes with and without metastatic cells. Whereas no significant changes were observed for B‐cell and natural killer (NK)‐cell subsets, metastatic lymph nodes had a significantly increased frequency of CD8 T cells and a skewing toward an effector/memory phenotype of CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
5
16
0
Order By: Relevance
“…Previous studies also showed that tumor cells could directly present antigens to CD8 T cells via MHC class I molecules, and initiating immune responses required DCs to exert antigen presentation [ 39 ]. Lymph nodes of metastatic breast cancer have a significantly increased proportion of CD8 T cells and a skewing toward an effector or memory phenotype of CD4 and CD8 T cells, indicating an ongoing immune response [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that tumor cells could directly present antigens to CD8 T cells via MHC class I molecules, and initiating immune responses required DCs to exert antigen presentation [ 39 ]. Lymph nodes of metastatic breast cancer have a significantly increased proportion of CD8 T cells and a skewing toward an effector or memory phenotype of CD4 and CD8 T cells, indicating an ongoing immune response [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, gene amplification and increased transcription of RAD54B were significantly associated with the prognosis of HCC, which was also manifested in BRCA. The high-risk HCC subtypes identified in this study were 36 Oxidative Medicine and Cellular Longevity analyzed to have higher sorafenib sensitivity and high expression of immune checkpoint molecules, suggesting that this population is more suitable for sorafenib combined with ICI therapy. However, in the above-mentioned high-risk subtype samples, while high RAD54B expression suggested a worse prognosis, it was significantly positively correlated with increased TMB/MSI and showed a worse prognosis in the sorafenib-treated group.…”
Section: Discussionmentioning
confidence: 84%
“…Regulation of T cell activation also plays a dominant role in tumor metastasis, especially in the immune microenvironment of early LNM. In metastatic sentinel lymph nodes, the effects of metastatic BRCA cells on the immune system focus at an early stage on sustained T-cell immune responses, depletion of effector T cells, and enhanced Treg-mediated immunosuppression [36][37][38]. In addition, γδ T cells can promote BRCA LNM through neutrophil-mediated CD8+ T cell suppression [39].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-related fibroblasts can tame immune cells to create a microenvironment suitable for tumor survival ( 41 , 42 ). The loss of memory T lymphocytes further aggravates the exhaustion of T cells, which is also an important cause of immune dysfunction in patients with tumors ( 34 , 43 ). These collective findings indicated that PCD-related lncRNAs impact the dysfunction of immune cells in CC immunity, thus providing a new platform for the development of novel immunotherapies.…”
Section: Discussionmentioning
confidence: 99%